Revisiting the Sapir–Whorf Hypothesis in Revolutionary Political Discourse: A Systematic Literature Review of Anti-American and Anti-Israeli Slogans in Iranian Media - Wicaksono, Anggar; Yusuf, Kamal (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study revisits the Sapir–Whorf Hypothesis within the context of revolutionary political discourse by examining anti-American and anti-Israeli slogans in Iranian media. The study aims to analyze how ideological language shapes political perception, collective identity, and sociocultural cognition through revolutionary narratives. This research employed a Systematic Literature Review (SLR) based on PRISMA 2020 guidelines by synthesizing relevant studies from Scopus-indexed journals and reputable academic databases published between 2015 and 2026. The analysis integrated perspectives from linguistic relativity, critical discourse analysis, political communication, propaganda studies, and media discourse.The findings reveal that revolutionary slogans in Iranian media function not merely as rhetorical expressions but also as sociocognitive instruments that normalize ideological values, construct enemy representations, and reinforce anti-hegemonic resistance narratives. The study further demonstrates that contemporary interpretations of the Sapir–Whorf Hypothesis increasingly emphasize ideological framing, symbolic repetition, and collective political cognition rather than strict linguistic determinism. The novelty of this study lies in its interdisciplinary integration of linguistic relativity theory with revolutionary political discourse and Iranian media studies. This study contributes theoretically by extending linguistic relativity into political communication studies and contributes methodologically through a systematic interdisciplinary synthesis connecting language, ideology, cognition, and geopolitical discourse.